Value-Based Quality Management in Higher Education: Rusydi Ahmad Tho’imah’s Perspective - Jamilatus Syarifah (Penerbit Presisi Pustaka, 2026)
Higher education quality management faces serious challenges amid increasing demands for accountability, transparency, and global competitiveness. In practice, quality assurance and accreditation are often understood in technocratic and administrative terms, thus failing to fully establish a sustainable culture of quality. This article aims to analyze the concept of value-based quality management in higher education, examine Rusydi Ahmad Tho'imah's thoughts on quality assurance and accreditation, and explain the relevance of these thoughts to the contemporary higher education quality assurance system. This study uses a qualitative approach with a literature review, with primary data sources in the form of Rusydi Ahmad Tho'imah's works and secondary data sources in the form of relevant national and international scientific journal articles. The data were analyzed using content analysis and thematic analysis to identify the concepts, principles, and implications of value-based quality management. The results of the study show that value-based quality management places quality as an institutional value and culture that is integrated into the entire process of the three pillars of higher education. Rusydi Ahmad Tho'imah's thinking on al-jawdah al-shāmilah emphasizes that quality assurance and accreditation are instruments of quality development oriented towards continuous improvement, not merely the fulfillment of administrative standards. This approach is highly relevant in strengthening the higher education quality assurance system to make it more meaningful, sustainable, and aligned with academic values and institutional ethics.